Analysis of the Influence of Social Capital On Entrepreneurial Orientation And Entrepreneurial Behavior: A Study On Startups In Jabodetabek - Gunawan, Rendy; Ikasari, Novita (LPPM of NAROTAMA UNIVERSITY, 2025)
Purpose: The purpose of this study is to analyze the impact of social capital on entrepreneurial orientation and entrepreneurial behavior of startup owners in the greater area of Jakarta, Bogor, Depok, Tangerang and Bekasi (Jabodetabek). Design/methodology/approach: This study applies a quantitative approach. The data collection was done via online questionnaire from April 2024 to June 2024 The 376 respondents were startup owners whose business was domiciled in Jabodetabek. SEM PLS was used to develop a model and analyze the data.Findings: The study finds that social capital significantly affected both entrepreneurial orientation and entrepreneurial behavior of startup owners, partially and simultaneously. Research implications: Social capital, in the form of robust social networks, plays an important role in enhancing entrepreneurial orientation and behavior, including proactiveness, innovation, and risk taking. Practical implications: This study shows the importance of strengthening social networks to support an entrepreneurial mindset and attitude. Entrepreneurs can leverage social capital to access information, resources, and opportunities. Originality/value: This study expands the understanding of how social networks, trust, and norms influence innovation, risk taking, and proactivity, providing practical value for entrepreneurs, organizations, and policymakers to optimize social capital in enhancing entrepreneurial mindset.Paper type: Research paper